2017
DOI: 10.1038/s41598-017-09174-5
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitivity enhancement of flexible gas sensors via conversion of inkjet-printed silver electrodes into porous gold counterparts

Abstract: This work describes a facile, mild and general wet chemical method to change the material and the geometry of inkjet-printed interdigitated electrodes (IDEs) thus drastically enhancing the sensitivity of chemiresistive sensors. A novel layer-by-layer chemical method was developed and used to uniformly deposit semiconducting single-wall carbon nanotube (SWCNT)-based sensing elements on a Kapton® substrate. Flexible chemiresistive sensors were then fabricated by inkjet-printing fine-featured silver IDEs on top o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Analysis of the effective surface revealed that the resulting structures are porous. Even though the porosity of the electrodes had no enhancing effect on DNA sensing in this work, other applications (e.g., glucose sensing [45]) may benefit from the relatively simple production process, which can be an attractive alternative to common fabrication methods like dealloying, template based synthesis [45] or chemical conversion of inkjet-printed Ag structures, which leads to only weakly cohesive porous gold [46].…”
Section: Discussionmentioning
confidence: 93%
“…Analysis of the effective surface revealed that the resulting structures are porous. Even though the porosity of the electrodes had no enhancing effect on DNA sensing in this work, other applications (e.g., glucose sensing [45]) may benefit from the relatively simple production process, which can be an attractive alternative to common fabrication methods like dealloying, template based synthesis [45] or chemical conversion of inkjet-printed Ag structures, which leads to only weakly cohesive porous gold [46].…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to the above‐mentioned subtractive technologies, additive manufacturing techniques (inkjet, screen, and 3D printing) offer extremely low cost, completely digital, and highly scalable manufacturing processes . Due to these advantages, additive manufacturing techniques have been used to realize sensors, transistors, RF inductors, RF capacitors, RF filters, RF identification (RFID) tags, and so on. There have only been a few reports on printed RF switches .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the NO 2 gas sensors showed good performance with a high sensitivity of ≈96% and recovery time of 30 s when exposed to 60 ppm NO 2 at room temperature. To enhance their sensitivity, the CNTs could be functionalized with conducting polymers that can interact with the target molecules or metal nanoparticles to change the contact resistance between the electrode material and the CNT channel …”
Section: Flexible Otftsmentioning
confidence: 99%